Health care Affordability and Associated Concerns Among Adults Aged 65 and above in Florida. (April 2022) - Wiltshire, Jacqueline; Garcia Colato, Edlin; Conner, Kyaien O.; Anderson, Erica; Orban, Barbara
Objective: This study assessed affordability of care in a diverse sample of Floridians aged ≥ 65 to ascertain concerns about health care costs. Methods: We surveyed 170 adults (40.6% white, 27.6% black, and 31.8% Hispanic) and conducted three race/ethnic-stratified focus groups ( n = 27). Results: Most participants had Medicare (97.1%). Among whites, 11.6% reported problems paying medical bills in the past 12 months versus 14.9% of blacks and 24.1% of Hispanics. In addition, 13% of whites, 19.2% of blacks, and 20.4% of Hispanics reported not getting needed prescription drugs because of costs. The most frequently identified concerns from the focus groups were the cost of prescription drugs, out-of-pocket expenses, and medical billing. Concerns about medical billing included understanding bills, transparency, timely postings, and uncertainty about who to contact about problems. Discussion: Our findings suggest that practices that help older adults effectively manage medical bills and costs may alleviate their concerns and guard against financial burdens.